Analisis Nilai Mutu Produk, Profitabilitas dan Sensitivitas Sarabba Bubuk di Kabupaten Enrekang - Nurmawati wati (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2026)
The objectives of the research are (1) to describe the criteria for assessing the quality value of the product and packaging of the instant sarabba powder, (2) to analyze the yield produced, (3) to analyze the profitability of the instant sarabba powder business, (4) to analyze the sensitivity value to changes in selling prices of the instant sarabba powder business. The data analysis methods used are descriptive and quantitative analysis, namely product and packaging quality analysis, profitability, and sensitivity. The research results show that (1) The product quality value shows an average liking score of 4, which means the product is well accepted by consumers, (2) The production yield reaches 72.6%, a high yield indicates efficiency in processing raw materials, (3) Business profitability of 21.34% is categorized as sufficient, generating adequate profits. However, the business needs to improve cost efficiency and marketing strategies to optimize profitability and minimize business risks, (4) Sensitivity analysis of changes in selling prices shows a value of 2.27, which means that business profits are greatly affected by changes in product prices. Overall, the instant powdered sarabba business is promising with products that are favored by the market, but it requires management and development strategies to be more sustainable and profitable.